(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Due to the often-late stage of gynaecological cancer diagnosis, substantial degrees of anguish are frequently felt. Understanding the causes of psychological discomfort is essential for designing solutions that specifically address those causes. This study is to assess distress and mental health in patients with gynaecological cancer. “The Beck Depression Inventory” and the “Mental Health Inventory” were used to evaluate psychological distress. Demographic variables are also been evaluated. 150 gynaecological cancer-patients are the participants of this study. More percentage (%) of participants are suffering from an advanced-stage of illness, usually stage III-IV. The diagnosis & the majority were presently undergoing treatment. More than half of women experienced high stress reactions to their disease and its treatment, and almost 1/5th of them expressed medium to extreme stages of anguish. Additionally, there was evidence to support the notion that psychological distress was higher among patients of 55 years of age are more prone, those with more advanced or recurring illness, and those who had received their gynaecological cancer diagnosis more recently. The distress and mental health study imply that women with gynaecological cancer should be thoroughly assessed to see if therapy for these symptoms is necessary since mental stress & stress reactions to illness are common within them.